2021
DOI: 10.1101/2021.05.18.21256801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Family Liaison Officer (FLO) role during the COVID-19 Pandemic

Abstract: Objectives: During the first wave of COVID-19 heavy restrictions were placed on hospital visitations in the United Kingdom. To support communication between families and patients a central London hospital introduced the role of the Family Liaison Officer. Communication within healthcare settings is often the subject of contention, particularly for patients families. During periods of crisis communication can become strained for patients and their families. We aimed to evaluate the rapid implementation of this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Brokering roles offer the opportunity to improve communication between healthcare teams and members of the patient's family, yet there are limited examples of such nonprofessional roles within the acute care settings. 5,9 The results of this study have identified the Previous research has raised confusion surrounding the introduction of new brokering roles such as FLOs, not only with the clinical team but with the postholders themselves as well as patients and their relatives. 5,9 It is clear from this study that the preparation of postholders and ward nursing teams was not sufficient before the commencement of the post and more clarity around the intention of this nonprofessional role was needed.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Brokering roles offer the opportunity to improve communication between healthcare teams and members of the patient's family, yet there are limited examples of such nonprofessional roles within the acute care settings. 5,9 The results of this study have identified the Previous research has raised confusion surrounding the introduction of new brokering roles such as FLOs, not only with the clinical team but with the postholders themselves as well as patients and their relatives. 5,9 It is clear from this study that the preparation of postholders and ward nursing teams was not sufficient before the commencement of the post and more clarity around the intention of this nonprofessional role was needed.…”
Section: Discussionmentioning
confidence: 89%
“…More recently, against the backdrop of the COVID‐19 pandemic when hospital visiting was halted, some healthcare organisations introduced new broker roles to bridge the visiting gap to ensure that patients and their relatives were able to remain in contact. An FLO role, using redeployed staff, was introduced at a central London hospital in the early stages of the first wave of the pandemic 9 . The views of patients and families are missing however, the FLOs reported the role had a very positive impact, for example, benefit of consistency of care to help build rapport and trust with patients, family and clinical staff 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential solution suggested by family members was a communications coordinator to allow medically qualified staff to concentrate on patient care. During the COVID‐19 pandemic, hospitals in the UK introduced Family Liaison Officers, and recent research supports the potential to standardize these roles 39 . We recognize the potential of family liaison officers, with the caveat that clinical care and complex treatment plans would still need to be communicated by clinical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Discharge processes 24 (49) 124 (39) • The discharge process was sometimes described as 'faultless' and 'impressive', with follow-up appointments made, referral to community services in place and 'detailed instructions' for themselves and the GP.…”
Section: Disorganized Discharge Processesmentioning
confidence: 99%